(untitled) - Besenius E; 2; 3; Cabri J; Delagardelle C; 4; Stammet P; 6; Urhausen A; 2; 7 (Deutsche Zeitschrift für Sportmedizin)
The aim of this project was to create a national database to determine sports-related sudden cardiac event (SCE) burden in Luxembourg. Systematic data collection was carried out from 2015 until 2019 (5 years). Cases of SCE met the following criteria: (1) any major cardiac adverse event, (2) occurring during or until one hour after a sports activity (3) on national territory or outside Luxembourg by a Luxembourgish resident or sports license holder. The victim or family were contacted to inquire on the SCE by means of a standardized questionnaire.In total, 43 SCE cases were registered. The incidence was 2.6 cases/year/100000 physically active inhabitants. The 43 events occurred in 41 persons (40 males, 1 female), at an average age of 49.7 years. Seventeen events were fatal. The most concerned sports were cycling (17 cases), followed by football (5), and running (4). Twenty-four victims suffered a sudden cardiac arrest, of which 16 received cardiopulmonary resuscitation (CPR). Eight (33%) of those survived. The survival rate was highest in patients receiving immediate CPR after SCE. The incidence of SCE related to sports in Luxembourg is relatively high and mainly affects middle-aged men during cycling. Bystander CPR significantly improves the chances of survival.Key Words: Cardiac Arrest, SCE, CPR, Chances of Survival